2015
DOI: 10.7314/apjcp.2015.16.17.7599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Indices in Lung Cancer Patients

Abstract: Background: In this study, we aimed to determine platelet indices such as platelet count (PLT), mean platelet volume (MPV), platelet distribution width (PDW), Plateletcrit (PCT) platelet count (PLT) in lung cancer cases, and evaluate any relationships between these parameters and stage or histologic types. Materials and Methods: This retrospective study covered 44 lung cancer patients and 47 healthy subjects. Platelet indices including PLT, PCT, MPV, PDW were estimated and compared with normal subjects. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 28 publications
6
42
3
Order By: Relevance
“…But previous studies of the MPV and PDW showed that this collateral distribution could change in various types of cancer (Okuturlar et al, 2015;Ozaksit et al, 2015). For example, a study of lung cancer patients reported that the MPV was lower and that the PDW was higher (Oncel et al, 2015), similarly to that what was found in the present study. Also, other studies found no statistically significant differences between the PDW value in neoplastic adnexal mass and breast cancer and PDW values in a control group (Ma et al, 2014;Okuturlar et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…But previous studies of the MPV and PDW showed that this collateral distribution could change in various types of cancer (Okuturlar et al, 2015;Ozaksit et al, 2015). For example, a study of lung cancer patients reported that the MPV was lower and that the PDW was higher (Oncel et al, 2015), similarly to that what was found in the present study. Also, other studies found no statistically significant differences between the PDW value in neoplastic adnexal mass and breast cancer and PDW values in a control group (Ma et al, 2014;Okuturlar et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have analysed the relationship between the MPV and cancer (Aksoy et al, 2008;Kumagai et al, 2015;Oncel et al, 2015). One study reported a considerable decrease in the MPV values in some types of cancer (Oncel et al, 2015). Others reported that a significant decrease in the MPV was associated with bone marrow metastasis and increased cell death in advanced-stage cancer (Aksoy et al, 2008;Kumagai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dincel O et al, found that PCT was significantly higher in patients with PTC than the BMG and control group (14). It is also reported that platelet indices may be useful to diagnose and follow-up cardiovascular, cerebrovascular, thromboembolic, and inflammatory diseases (36). In the current study, PCT values were significantly higher in both BMG and PTC groups than the control group.…”
Section: Discussionsupporting
confidence: 54%
“…A study concerning the MPV in patients diagnosed with different cancers found a significant reduction in MPV values between patients at the time of diagnosis of a thrombotic event and control groups at the time of diagnosis [33]. Additionally, several studies have found the MPV value to be significantly lower in cancer patients with lung cancer or metastasis to the bone marrow compared to control groups [23, 34]. Furthermore, two recent studies showed that low MPV levels correlated with unfavourable prognosis in NSCLC [17, 18].…”
Section: Discussionmentioning
confidence: 99%